Sex-related, growth–climate association of Araucaria angustifolia in the neotropical ombrophilous woodlands of Argentina - Cattaneo, Nicolás (2013)
Araucaria angustifolia is a dioecious dominant tree in araucaria forests in Brazil and Argentina, South America. The species is nowadays critically endangered by deforestation and global climate change. The goal of this study was to analyse the dynamics of radial growth in this species and its association with climatic variables, according to the sex, at its western range boundary in Argentina. Standard dendrochronological techniques were applied on stem disks from female and male trees. Xylem anatomical anomalies made the tree-ring dating process difficult. Female and male trees showed growth patterns that changed over time, not being significant in the 1950–1990 period and highly significant from the 1990s onwards (p < 0.1) when female trees had a higher growth rate. Female and male trees showed a different association with climatic variables. No significant effect of temperature and precipitation was identified on female trees. For male trees, rainfall had a positive effect in August, before the growing season, and a negative effect at the end of the growing season (March). Temperature had a negative effect on male trees, before and during the growing season (February and January, respectively). No effect of SOI was detected on both sexes. Results emphasised the usefulness of A. angustifolia for dendrochronological studies and the value of dioecious species for the study of sex-related growth–climate association.